1986
DOI: 10.1111/j.1475-097x.1986.tb00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Venous plasma adrenaline response to orthostatic syncope during tilting in healthy men

Abstract: The effect of transient cerebral ischaemia connected with acute orthostatic hypotension on plasma adrenaline and noradrenaline levels was studied in seven healthy male volunteers during tilt. Sublingual administration of 1 mg nitroglycerin was used to block peripheral vascular reflexes and thus to provoke orthostatic intolerance. A consistent increase in plasma adrenaline concentrations (from 19.2 to 104.3 pg/ml on average, P less than 0.01) was found in six subjects who developed clinical signs of collapse af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…At syncope, much of the vasodilatation can be accounted for by withdrawal of sympathetic vasoconstrictor activity [19][20][21]. The increase in plasma epinephrine, the putative direct beta-adrenergic vasodilator, occurs only at syncope but not before [22][23][24]. However, local beta-adrenergic blockade does not affect forearm vasodilatation at syncope [25,26].…”
mentioning
confidence: 95%
“…At syncope, much of the vasodilatation can be accounted for by withdrawal of sympathetic vasoconstrictor activity [19][20][21]. The increase in plasma epinephrine, the putative direct beta-adrenergic vasodilator, occurs only at syncope but not before [22][23][24]. However, local beta-adrenergic blockade does not affect forearm vasodilatation at syncope [25,26].…”
mentioning
confidence: 95%
“…Previous investigators [9][10][11][12][13] have reported significant increases in EPI during orthostatic intolerance in young individuals. Indeed, plasma EPI concentrations at the termination of orthostatic stress have been reported to be two-to eight-fold greater in young subjects experiencing symptomatic hypotension [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, plasma EPI concentrations at the termination of orthostatic stress have been reported to be two-to eight-fold greater in young subjects experiencing symptomatic hypotension [9][10][11][12][13]. Due to its ability to cause peripheral vasodilation and stimulate cardiac vagal fibres, EPI has been implicated as a possible mechanism responsible for orthostatic intolerance [3,11,[13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations